Preparation method of carbon foam composite phase change energy storage material - ZHONG CHANGHE; CHEN BIN; LIN QILANG (2018)
The invention belongs to the technical field of phase change energy storage materials, and mainly relates to a preparation method of a composite phase change energy storage material with high performance. The carbon foam composite phase change energy storage material is prepared by impregnating the energy storage material into foam carbon with a vacuum impregnation method, wherein the carbon foamand a solid-liquid phase change storage materials subject to surface treatment and acid etching treatment are basic materials. By using the preparation method, the obtained composite material has a faster speed to respond to thermal conductivity, a higher level of latent heat storage and excellent cycling stability; meanwhile the industrial application prospect is wide for a simple preparation process, simple equipment and low production cost required by the method. 本发明属于相变储能材料技术领域，主要涉及种高性能的复合相变储能材料的制备方法。本发明以表面处理和酸腐蚀处理后的泡沫炭、固-液相变储能材料为基础原料，采用真空浸渍的方法将储能材料浸渍入泡沫炭，制备得到泡沫炭复合相变储能材料。本发明获得的复合材料导热能力响应的速度更快，在潜热存储上也达到了个较高的水平，具有优异